DAMPAK BENCANA TERHADAP ANAK USIA DINI DAN INTERVENSI PSIKOSOSIAL - Salam, Abdul; Nurhadah; Husen (Musawa: Journal for Gender Studies, 2026)
Disasters can have a significant impact on early childhood, both physically, emotionally, socially, and psychologically. This article discusses the impact of disasters on children aged 0–6 years and the importance of psychosocial interventions to support their recovery process optimally. The research uses a descriptive qualitative approach through observation of children's behavior, interviews with parents or caregivers and volunteers, and analysis of children's play activities and work. The results show that effective and structured interventions refer to five main principles, namely ensuring safety, promoting calmness, strengthening connectedness, encouraging self- and group efficacy, and instilling hope. This principle is manifested through moving children to a safe place, providing play and educational activities, active involvement of parents and the community, and symbolic activities that are able to arouse enthusiasm and confidence. The psychological condition of post-disaster children is affected by a shaken sense of security, weakened self-positivity, disrupted meaning of life, and the quality of social support during recovery. Therefore, interventions need to include emotional, social, educational, and family aspects on an ongoing basis. A sensitive approach to the stage of child development is expected to be able to reduce symptoms of trauma, strengthen resilience, restore social function, and help children adapt to the environment in a healthy and gradual manner, according to the individual needs and cultural context of the communities affected by local disasters.